When Busy Is Less Indulging: Impact of Busy Mindset on Self-Control Behaviors - Kim, Jeehye Christine; Wadhwa, Monica; Chattopadhyay, Amitava (Journal of Consumer Research, 2019)
An increasing number of consumers, in recent times, have reported feeling busier than ever. The current research examines how the subjective perception of busyness—which is referred to as a busy mindset in the current research —impacts consumers’ decision-making. Building on different streams of research in sociology and self-view, the current research proposes that a busy mindset bolsters people’s sense of self-importance, which, in turn, can increase self-control. Thus, a busy mindset is predicted to facilitate people’s ability to exert self-control. Seven studies, including a field study, provide support for this busy mindset hypothesis across various self-control domains. Findings from these studies provide support for the underlying process related to self-importance in multiple ways, while also addressing alternative accounts related to stress and the desire for productivity. Finally, findings from the current research delineate important managerially relevant boundary conditions for the proposed busy mindset effect.